THE INFLUENCE OF WORK COMPETENCE AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE MINISTRY OF TRANSPORTATION DIRECTORATE GENERAL OF SEA TRANSPORT OFFICE OF CLASS III PORT ORGANIZATION UNIT RIVERSIDE LUMPUR - Fane, Sugeng Mianto; Darmawan, Sukaria; Widiatmoko, Kukuh (Universitas Teknokrat Indonesia, 2024)
The purpose of the research is to find out the influence of competence and work discipline on the performance of employees in the Ministry of Transportation of the Directorate General of Marine Transportation Office of the II Sungai Lumpur Port I organization Unit. The problem in this study is, “Are the competence and discipline of work partially and simultaneously to performance?” Hypothesis testing uses multiple linear regression analysis, through the T-test and the F-test, with the intention to determine the effect of independent variables on dependent variables at a 95% confidence level (a = 0.05). The results of the test on the T-test on the competency variable have a positive effect on performance, the visible value of t count (5.287) > t table (2,032) and significance (0.00) below or smaller than 0, 05, while in the disciplinary variable the work has a positive effect on performance, the visible value of t count (3,062) > t table (2,032) and significance (0.00) below or smaller than 0, 05. In testing on the F test on the competence of the variables of the work discipline and has a positive effect on performance, the visible value of Fhitung (6,616) > F table (3,252), and significance (0.01) below or smaller than 0, 05